PERBEDAAN ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SETELAH PENGUMUMAN PEMENANG AWARD TAHUN 2014 PADA PERUSAHAAN YANG LISTING DI BURSA EFEK INDONESIA - Apriyanti .; Heny Sidanti (Universitas Muhammadiyah Ponorogo, 2016)
This research aimed to provide empirical evidence a difference of abnormal return and Trading Volume Activity by before and after receiving the award ARA, ICA, ISRA on companies listed in the Indonesia Stock Exchange in 2014.This research is secondary data in the form of the company's daily closing price and number of outstanding shares can be obtained from www.idx.co.id and Indonesian Capital Market Directory (ICMD). With a sample of ARA award recipient, ICA, ISRA on companies listed in the Indonesia Stock Exchange in 2014. The data analysis method used in this study is event study analysis techniques and different test ttest.The results shows that there is no difference of abnormal return and trading volume of activity before and after the announcem ent of the award Annual Report Award (ARA), Indonesian CSR Award (ICA), and the Indonesian Sustainability Reporting Award (ISRA) in 2014.